Impact of magnetite on Fe3O4/Activated Carbon (AC)/ZnO Nanocomposite for Photodegradation of Rhodamine B - Bemis, Restina; Marlinda, Lenny; Rahmi; Pratiwi, Nurul; Wibimanyu, Putu Adityo; Lia Anggresani (Department of Chemistry, Faculty of Science and Technology Universitas Jambi, 2025)
Rhodamine B is an organic dye commonly used in the textile industry, but it is toxic. Therefore, a photodegradation method using Fe3O4/activated carbon (AC)/ZnO nanocomposite is necessary to address environmental issues caused by rhodamine B. The Fe3O4/AC/ZnO nanocomposite has been successfully synthesized using the sonication method. Iron sand is used as a source of magnetite (Fe3O4), coconut shells as a source of activated carbon, and Zinc nitrate as a source of ZnO. XRF results show that the Fe content in iron sand is 74.10%. The ratio of Fe3O4 addition used in Fe3O4/AC/ZnO nanocomposite is 0:1:1; 1:1:1; 2:1:1; 3:1:1; 4:1:1. XRD characterization shows that the 1:1:1 ratio of Fe3O4/AC/ZnO nanocomposite has the smallest crystal size of 48.17 nm. The addition ratio of Fe3O4 does not affect the structure of the formed Fe3O4/AC/ZnO nanocomposite. Fe3O4/AC/ZnO nanocomposite is formed at 2theta 30.23°; 35.60°; 57.11°; and 62.83° for Fe3O4, peak broadening at 26.72° and 44.71 for AC, and 31.82°; 34.47°; 36.30°; 47.59°; 56.63°; 62.89° and 67.98° for ZnO. SEM results show particle sizes of 57.95 nm for ZnO and 42.74 nm for Fe3O4/AC/ZnO 1:1:1 nanocomposite. VSM showed saturation magnetism of 4.41 emu/g for Fe3O4/AC/ZnO 1:1:1 nanocomposite and 28.8 emu/g for Fe3O4. The photocatalytic test showed that the Fe3O4/AC/ZnO 1:1:1 nanocomposite had the best % degradation of rhodamine B, at 96.1%, under sunlight.